Electrochemical determination of an anti-hyperlipidimic drug pitavastatin at electrochemical sensor based on electrochemically pre-treated polymer film modified GCE - Umar J. Pandit; Gowhar A. Naikoo; Mehraj Ud Din Sheikh; Gulzar A. Khan; K.K. Raj; S.N. Limaye (Elsevier, 2017)
An electrochemically pretreated silver macroporous (Ag MP) multiwalled carbon nanotube modified glassy carbon electrode (PAN-Ag MP-MWCNT-GCE) was fabricated for the selective determination of an anti-hyperlipidimic drug, pitavastatin (PST). The fabricated electrochemical sensor was characterized by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The fabricated electrode was employed in quantifying and determining PST through differential pulse adsorptive stripping voltammetry (DPAdSV) and CV. The electrode fabrication proceeded with remarkable sensitivity to the determination of PST. The effect of various optimized parameters such as pH, scan rate (ν), accumulation time (tacc), accumulation potential (Uacc) and loading volumes of Ag MP-MWCNT suspension were investigated to evaluate the performance of synthesized electrochemical sensor and to propose a simple, accurate, rapid and economical procedure for the quantification of PST in pharmaceutical formulations and biological fluids. A linear response of PST concentration in the range 2.0×10−7-1.6×10−6 M with low detection (LOD) and quantification (LOQ) limits of 9.66±0.04 nM and 32.25±0.07 nM, respectively, were obtained under these optimized conditions.